Lipid -Lowering Effect of Polysaccharide (Pectin) of Viscum album L. Plant in Rats - Dmitry Pozdnyakov; Similla Adzhiakhmetova; Nadezhda Chervonnaya; Stanislav Oganesyan (College of Pharmacy University of Baghdad, 2023)
Disturbances of lipid metabolism is a predisposing factor of cardiovascular diseases, which are accompanied by high mortality rates of the population - ischemic heart disease and ischemic stroke. Plant polysaccharides can be promising remedies for correction of lipid imbalance. In this regard, the aim of the study was to assess the hypolipidemic activity of polysaccharides isolated from the leaves of mistletoe. The test-object was the leaves of the white mistletoe (Viscum album L.) growing on the apple (Malus domestica Borkh.), and the pear (Pyrus communis L.). Polysaccharides (water-soluble polysaccharides and pectin substances) were quantitatively determined by the gravimetric method followed by reprecipitation from ethanol. The qualitative composition was evaluated by thin layer chromatography. Functional groups in polysaccharides were determined by titrimetric method. The hypolipidemic activity of the obtained polysaccharides was determined under oral administration at a dose of 100 mg / kg in Wistar rats by the change of the concentration of total cholesterol, triglycerides, LDL and HDL cholesterol. The change of the content of cholesteryl ester transfer protein and Niemann-Pick C1-Like1 protein was also determined. As a result, it was found that among the polysaccharides in the leaves of mistletoe, pectin substances are predominate, which belong to the group of low-esterified pectins. A significant content of free carboxyl groups in pectins from the leaves of mistletoe was also found. The study of hypolipidemic activity showed that, among the polysaccharides of mistletoe leaves, pectin substances exert a more pronounced effect on lipid metabolism, the use of which reduced the content of triglycerides, total cholesterol and LDL cholesterol with an increase in LDL cholesterol in rats, probably due to a decrease in the activity of cholesteryl ester transfer protein and Niemann-Pick C1-Like1 protein. At the same time, at the level of the trend, mistletoe pectins showed a higher level of activity than analogous compounds obtained from the leaves of host-plants. It should be noted that the severity of the pharmacological effect of mistletoe pectins did not depend on the host-plants. Thus, based on the obtained results, it can be assumed that pectins obtained from the mistletoe leaves can be a potentially effective and safety hypolipidemic agent.